Nerve ultrasound reference data in children from two to seven years. Issue 4 (April 2020) - Schubert, Charlotte; Grimm, Anna-Sophie; Stahl, Jan-Hendrik; Küpper, Hanna; Kegele, Josua; Wittlinger, Julia; Serna-Higuita, Lina; Winter, Natalie; Groeschel, Samuel; Grimm, Alexander
Highlights: Nerve size in children correlates significantly with age; influence of BMI and gender is limited. Side-to-side differences and intranerve-cross-sectional area (CSA)-variability are useful additive information. Grey-scale analysis enables quantification of nerve echo intensity. Abstract: Objective: We examined selected peripheral and spinal nerves of children aged between two and seven years. Method: High resolution ultrasound was performed in 116 children (2–7 years of age) at 19 predefined landmarks of median, ulnar, tibial, fibular, sural and radial nerves, the vagus as well as cervical spinal nerve 5 and 6. Further, side-to-side measuring and grey-scale analysis was done at selected nerve sites. Results: Nerves of children were on average smaller than those of adults. Nerve growth correlates significantly with age in all nerves, the mean values were similar in the age of two to four years and five to seven years. Body mass index (BMI) and gender showed moderate effect at some nerve sites, however not uniformly in all. A side-to-side difference of up to 30% in median, and up to 20% in tibial nerve can occur in healthy individuals. Grey-scale analysis for echointensity has been performed in median, ulnar and tibial nerves. Conclusion: Nerve size increases with age, BMI and gender have moderate effect. A side-to-side-difference of up to 30% can exist. Significance: Reference values of nerve cross-sectional area, side-to-side-difference and echo intensity are necessary to detect nerve pathology in children as well as in adults.